A Thiadiazole‐Based Conjugated Polymer with Ultradeep HOMO Level and Strong Electroluminescence Enables 18.6% Efficiency in Organic Solar Cell. Issue 35 (21st July 2021) - Zhang, Tao; An, Cunbin; Bi, Pengqing; Lv, Qianglong; Qin, Jinzhao; Hong, Ling; Cui, Yong; Zhang, Shaoqing; Hou, Jianhui
Abstract: Under the premise of ensuring favorable bulk heterojunction morphology in organic solar cells (OSCs), conjugated polymer donors with deep‐lying highest occupied molecular orbital (HOMO) levels are highly important to improve power conversion efficiencies (PCEs) by reducing photovoltage loss. However, the development of such materials has lagged. Herein, a thiadiazole‐based conjugated polymer, PB2F is reported, which has a very deep HOMO level of −5.64 eV, and high electroluminescence quantum efficiency of 3.9 × 10 −3 . In OSCs, the PB2F‐based OSC gives an excellent PCE of 14.5% with an ultrahigh open‐circuit voltage ( V OC ) of 0.957 V by blending with an electron acceptor of IT‐4F. More importantly, the PB2F as a third component is added into the PBDB‐TF:BTP‐eC9 blend to achieve an outstanding PCE of 18.6% (certified PCE 18.2%), which is one of the highest PCEs in OSCs. Abstract : A thiadiazole‐based polymer donor (PB2F) with an ultradeep highest occupied molecular orbital level and high electroluminescence is reported. In organic solar cell (OSC) devices, PB2F exhibits a power conversion efficiency (PCE) of 14.5% after blending with IT‐4F, one of highest values among the IT‐4F‐based OSCs, and an outstanding PCE of 18.6% in the context of ternary OSC.